2007
DOI: 10.4161/cbt.6.2.3629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of celecoxib on E-cadherin, VEGF, microvessel density and apoptosis in gastric cancer

Abstract: Cyclooxygenase-2 (COX-2) plays a crucial role in the development and invasion of gastric cancer. COX-2 inhibitors have been shown to be chemopreventive against gastrointestinal cancers. In vitro studies have suggested that the mechanisms may be related to induction of apoptosis and inhibition of angiogenesis. COX-2 may also have impact on E-cadherin. In our study we investigate the effect of Celecoxib on expression of E-cadherin and serum soluble E-cadherin, as well as on apoptosis and angiogenesis in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…As VEGF is a potent angiogenic factor, enhancing tumor angiogenesis and contributing to tumor progression and metastasis, and COX-2 has been reported to regulate the expression and function of VEGF in cancers, the observed close correlation between the serum levels of VEGF and COX-2 indicates that blocking COX-2 may help reduce the neovascularization required for tumor growth. This observation is consistent with the findings of previous studies (17). As such, the serum levels of VEGF and COX-2 may serve as valuable biomarkers for the assessment of therapeutic benefit in gastric cancer patients receiving anticancer therapy.…”
Section: Discussionsupporting
confidence: 92%
“…As VEGF is a potent angiogenic factor, enhancing tumor angiogenesis and contributing to tumor progression and metastasis, and COX-2 has been reported to regulate the expression and function of VEGF in cancers, the observed close correlation between the serum levels of VEGF and COX-2 indicates that blocking COX-2 may help reduce the neovascularization required for tumor growth. This observation is consistent with the findings of previous studies (17). As such, the serum levels of VEGF and COX-2 may serve as valuable biomarkers for the assessment of therapeutic benefit in gastric cancer patients receiving anticancer therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the effect of celecoxib on cell cycle regulation and cell death (13,15), many other celecoxibresponsive genes, such as CDC2, CDC25A, GADD45A, Figure 4. Enriched functional categories and pathways in colorectal cancer cell lines following treatment with celecoxib.…”
Section: Discussionsupporting
confidence: 58%
“…In particular, specific proteins and molecular pathways, affecting cell cycle progression and apoptosis, have been extensively studied and shown to be targeted by celecoxib (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Celecoxib in conjunction with chemotherapy reduced VEGF in mice implanted with a colon cancer cell line and also increased IFN-gamma, which is important for antitumor immunity [77]. Zhou et al reported that post-operative gastric cancer patients given celecoxib had reduced VEGF levels in cancerous tissue compared to those that received surgical intervention alone [78]. As previously mentioned, Cox-2 expression in Hodgkin's lymphoma correlated with a greater degree of angiogenesis [3].…”
Section: Cox-2/pge 2 Promotes Angiogenesis and Metastasismentioning
confidence: 97%